DEPENDENCE OF THE EFFECTIVENESS OF MANAGERS OF GENERAL EDUCATIONAL ORGANIZATIONS ON CAREER STAGES - Koshevenko, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article examines the problem concerning the effectiveness of managers of general education organizations. There is no universal methodology for the assessment of effectiveness of activity of managers of general education organizations and no determined factors affecting any effectiveness indicator. The aim of this study is to analyse the effectiveness of managers of a general education organization at different stages of their careers. The main methods of this research are the system analysis, the questionnaire survey and the factor analysis. The author analyses the dependence of the effectiveness indicators of managers of general education organizations on the career stages.  The effectiveness evaluation was carried out according to the author's methodology and was based on the data of general education organizations in the Smolensk region.Managers of general education organizations at the establishment stage of a career haven't sufficiently formed public relations and developed educational activities. Managers at the advancement stage do not pay enough attention to building the career of employees of the educational organization.  Transfer of experience to youth, their adaptation in the team, support in research work, assistance in building a career are not sufficiently typical for school managers at the maintenance stage of careers.  Managers at the withdrawal stage of a career have a low level of information culture, lack motivation to use new technologies and progressive ideas.